The lost city of Z : [compact disc, unabridged] : a tale of deadly obsession in the Amazon - Grann, David (Random House Audio, 2009)
Interweaves the story of British explorer Percy Fawcett, who vanished during a 1925 expedition into the Amazon, with the author's own quest to uncover the mysteries surrounding Fawcett's final journey and the secrets of what lies deep in the Amazon jungle.